Answers

2016-07-13T21:02:13+08:00
Let's solve your equation step-by-step.(s+6)2=15Step 1: Simplify both sides of the equation.s2+12s+36=15Step 2: Subtract 15 from both sides.s2+12s+36−15=15−15s2+12s+21=0Step 3: Use quadratic formula with a=1, b=12, c=21.s=−b±b24ac2as=(12)±(12)24(1)(21)2(1)s=−12±√602s=−6+√15 or s=−6√15Answer:s=−6+√15 or s=−615
0
2016-07-13T23:14:06+08:00
  (s + 6)²    =    15
  (s+ 6)      =  + or  - √15      / take the sq rt of both sides
   s     =  - 6 + √15       or     - 6 - √15
       this is the short and easy way
     
1 5 1